On the Coexistence of Democracy and Monarchy: A Constitutional Study and the Constitutional Strains in Thailand - Thaewanarumitkul, Prinya (Thammasat Review, 2026)
According to democracy rankings, half of the 20 highest-ranked democracies are monarchies, while 50 of 59 authoritarian regimes are republics. This suggests that a constitutional monarchy – a system that combines democratic governance with a monarch who holds no executive power – can sustain a high level of democracy. In such systems, the prime minister and cabinet govern, while the monarch remains immune from prosecution, with accountability resting on those who act in the monarch’s name. Thailand, which has experienced 13 coups and adopted 20 constitutions, illustrates how instability arises when coup leaders seek royal consent and the judiciary legitimizes their actions. The image of royal neutrality was weakened after the coups of 2006 and 2014, particularly under the new monarch, largely because the coup makers repeatedly invoked royal authority to justify their actions. For democracy to succeed in Thailand, strict adherence to the principle of “The King Can Do No Wrong” by all institutions is essential. The judiciary must cease legitimizing coups, the Constitutional Court must uphold the rule of law to safeguard both the monarchy and democracy, and the 2017 Constitution – with its undemocratic mechanisms, such as the Senate and the excessive power of the Constitutional Court – must be rewritten.